Diagnostic assessment by fluorescein visualization of skin cancer lesion margins and surgical treatment of malignant skin tumors of the external nose - A. F. Yevcheva (Journal of Ophthalmology, 2022)
Purpose: To assess the diagnostic information value of chlorin e6 fluorescence visualization of cancer lesion margins in the radical surgical removal of malignant lesions of the external nose.